2016
DOI: 10.1039/c5ra22211g
|View full text |Cite
|
Sign up to set email alerts
|

Absorbance response of a graphene oxide coated U-bent optical fiber sensor for aqueous ethanol detection

Abstract: In this work, the dynamic change of the absorbance for aqueous ethanol detection based on a graphene oxide coated U-bent optical fiber sensor was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 31 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…In Figure 5 , the shifts in nm of S0, SGO1b, SGO2b and SGO4b LMR peaks are represented as a function of the ethanol concentration of the solutions. The responses recorded as ethanol concentrations were increased and then decreased again confirmed that the sensors present high repeatability and reversibility, improving other works found in the literature [ 27 ]. There was no obvious hysteresis in the response since the maximum variation between the measurements was only 2 nm and the distribution of the variance was random.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In Figure 5 , the shifts in nm of S0, SGO1b, SGO2b and SGO4b LMR peaks are represented as a function of the ethanol concentration of the solutions. The responses recorded as ethanol concentrations were increased and then decreased again confirmed that the sensors present high repeatability and reversibility, improving other works found in the literature [ 27 ]. There was no obvious hysteresis in the response since the maximum variation between the measurements was only 2 nm and the distribution of the variance was random.…”
Section: Resultssupporting
confidence: 84%
“…However, as a reference, recent works based on other phenomena showed rise and fall times of 40 and 70 s [ 25 ], 13 and 6 s [ 26 ], more than 10 min [ 37 ]. Authors could just find a work presenting similar dynamic times [ 27 ]. From these results, it can be concluded that the sensor presented here shows a fast reaction and recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the AgNPs/PCu@Si was rinsed by deionized water, and dried in the N 2 atmosphere. In order to control the number of layers of the GO, we choose to control the concentration and volume of the GO suspension, then the 50 μL and 0.5 mg/mL GO (obtained using the modified Hummers method22) suspension was deposited on the surface of the AgNPs/PCu@Si substrate by a dip-coating method. The prepared GO/AgNPs/PCu@Si substrate sealed in the nitrogen atmosphere was ready for the SERS measurements.…”
Section: Methodsmentioning
confidence: 99%
“…U-shaped probes have been demonstrated to have a 10-fold improvement in absorbance sensitivity over straight probes [37]. The use of U-shaped optical fiber as chemical probes seems to be popular over the last two decades, with the fiber used in probes for various chemicals and features of chemicals, including benzene [38], ethanol [39][40][41], toluidine blue [42], pH levels [43], glucose [44,45], and salt [46], but few of studies as a biosensor especially in miRNA of cancer. The sensitive property of U-shaped optical fiber to the external environment is quite suitable for low-concentration bio-detectors analytics.…”
Section: Introductionmentioning
confidence: 99%